Addicted to the Holocaust – Bernice Eisenstein’s Ways of Coping with Troublesome Memories in I Was a Child of Holocaust Survivors - Drewniak, Dagmara (Studia Anglica Posnaniensia, 2016)
In her I Was a Child of Holocaust Survivors published in Canada in 2006, Bernice Eistenstein undertakes an attempt to cope with the inherited memories of the Holocaust. As a child of the Holocaust survivors, she tries to deal with the trauma her parents kept experiencing years after WWII had finished. Eisenstein became infected with the suffering and felt it inescapable. Eisenstein’s text, which is one of the first Jewish-Canadian graphic memoirs, appears to represent the voice of the children of Holocaust survivors not only owing to its verbal dimension, but also due to the drawings incorporated into the text. Therefore, the text becomes a combination of a memoir, a family story, a philosophical treatise and a comic strip, which all prove unique and enrich the discussion on the Holocaust in literature. For these reasons, the aim of this article is to analyze the ways in which Eisenstein deals with her postmemory, to use Marianne Hirsch’s term (1997 [2002]), as well as her addiction to the Holocaust memories. As a result of this addiction, the legacy of her postmemory is both unwanted and desired and constitutes Bernice Eisenstein’s identity as the eponymous child of Holocaust survivors.